Seroprevalences of Hepatitis B Virus and Hepatitis C Virus among Participants of an Asian Health Fair in the Lower Mainland, British Columbia - Stephen Ip; Jo-Ann Ford; Kirby Lau; Vladimir Marquez; Marisa Guan; Carolyn Klassen; Jessica Chan; WC Peter Kwan; Mel Krajden; Eric M Yoshida (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: The seroprevalences of hepatitis B virus (HBV) and hepatitis C virus (HCV) are 0.4% and 0.8%, respectively, in Canada, but varying rates have been reported in different populations.